2012
DOI: 10.1002/hed.23130
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of protease‐activated receptor‐1 expression in human buccal fibroblasts stimulated with arecoline

Abstract: PAR-1 expression is significantly upregulated in areca quid chewing-associated OSF. Arecoline-induced PAR-1 expression was downregulated by NAC, LY294002, herbimycin A, NS398, and PD98059.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 63 publications
(86 reference statements)
0
6
0
Order By: Relevance
“…During the initiation and progression of many fibrotic diseases, activation of PAR‐1, the major thrombin‐activated receptor in humans, plays an important role . Tsai et al have demonstrated that PAR‐1 expression also contributes to the pathogenesis of areca quid chewing‐associated OSF. PAR‐1 deficiency protects against injury‐induced lung inflammation and fibrosis by diminishing the levels of proinflammatory and profibrotic mediators, such as monocyte chemoattractant protein‐1, TGF‐β, and CCN2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the initiation and progression of many fibrotic diseases, activation of PAR‐1, the major thrombin‐activated receptor in humans, plays an important role . Tsai et al have demonstrated that PAR‐1 expression also contributes to the pathogenesis of areca quid chewing‐associated OSF. PAR‐1 deficiency protects against injury‐induced lung inflammation and fibrosis by diminishing the levels of proinflammatory and profibrotic mediators, such as monocyte chemoattractant protein‐1, TGF‐β, and CCN2 .…”
Section: Discussionmentioning
confidence: 99%
“…9 We have previously shown that PAR-1 is solely responsible for the thrombin-induced CCN2 synthesis in BMFs. 8 Tsai et al 12 have demonstrated significantly higher PAR-1 expression in OSF specimens and that arecoline elevates PAR-1 expression in BMFs. These discoveries imply the promising role of PAR-1 as a pharmacological target for OSF intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical diagnosis was confirmed by histopathological examination of the biopsy specimens. Fibroblast cultures were grown and maintained according to the procedures described previously . Cell cultures between the third and eighth passages were used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical diagnosis was confirmed by histopathological examination of the biopsy specimens. Fibroblasts were cultured using an explant technique as described previously . The tissues were minced using sterile blades into small fragments and washed twice in phosphate buffer saline (PBS) supplemented with antibiotics (100 U/ml penicillin, 100 μg/ml streptomycin, and 0.25 μg/ml of fungizone).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we found that arecoline, a major areca nut alkaloid, could increase human buccal mucosa fibroblasts (BMFs) proliferation resulting in fibrotic change . Moreover, the augmentation of vimentin , cyclooxygenase‐2 , tissue inhibitor metalloproteinase‐1 , plasminogen activator inhibitor‐1 (PAI‐1) , interleukin‐6 , keratinocyte growth factor‐1 , insulin‐like growth factor‐1 , NF‐κB , cystatin C , heat shock protein 47 , heme oxygenase‐1 , S100A4 , and protease‐activated receptor‐1 expression may contribute to the extracellular components (ECM) accumulation in areca quid chewing‐related OSF. Recently, we reported that ZEB1 may participate in the pathogenesis of areca quid‐associated OSF by activating the α‐smooth muscle actin promoter and inducing myofibroblast transdifferentiation from BMFs .…”
Section: Introductionmentioning
confidence: 99%